Preliminary practice of multidisciplinary cooperative vaccination management model for pediatric patients with hematological and oncological diseases - Ruan, H S (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To preliminarily establish the multidisciplinary cooperative vaccination management model for pediatric patients with hematological and oncological diseases, and to explore its feasibility. Methods: In this prospective study a total of 150 children with hematological and oncological diseases visited immunization clinic of Shanghai Children's Medical Center from March 2017 to August 2018 were enrolled in this study. After establishing the multidisciplinary team, designing vaccination plan, staff training, implementation and quality control, a multidisciplinary immunization clinic was set up and the vaccination plan were implemented. The implementation rate of vaccination immunization, the HBsAb level and serum hepatitis B surface antibody (HBsAb) level before and after treatment, the HBsAb level and serum immunoglobulin G antibody (IgG) levels of measles, mumps, rubella (MMR) before and 6 months after immunization, the vaccine-related adverse reactions were assessed prospectively. Chi-square test or Fisher exact test was used to compare the differences of antibody level. Results: A total of 124 cases had been vaccinated as planned, with a coverage rate of 82.7%. Among these cases, the difference of HBsAb positive rate before and after treatment was significant (62.9% (78/124) vs.13.7% (17/124), χ²= 63.489, P<0.01). In 64 cases that completed three doses of hepatitis B immunization, there was a significant difference in HBsAb positive rate before and 6 months after immunization (6.3% (4/64) vs. 98.4% (63/64), P<0.01). In 40 cases that completed MMR immunization, the IgG antibody positive rate for measles (22.5% (9/40) vs. 82.5% (33/40), χ²=31.746,P<0.01), mumps (22.5% (9/40) vs.82.5% (33/40), χ²=28.872,P<0.01), rubella (25.0% (10/40) vs.62.5% (25/40), χ²=11.429, P<0.01) before and 6 months after immunization were significantly different. Of the 421 doses of immunization, 25 (5.9%) doses reported controlled systemic or local adverse event. Conclusions: The immunization of pediatric patients with hematological and oncological diseases is of great importance. The newly-developed multidisciplinary cooperation immunization model for Chinese children with hematological and oncological diseases is feasible, and the immunization protocol is safe and has a certain effect